A short summary of evaluatology: The science and engineering of evaluation - Jianfeng Zhan (BenchCouncil Transactions on Benchmarks, Standards and Evaluations, 2024)
Evaluation is a crucial aspect of human existence and plays a vital role in each field. However, it is often approached in an empirical and ad-hoc manner, lacking consensus on universal concepts, terminologies, theories, and methodologies. This lack of agreement has significant consequences. This article aims to formally introduce the discipline of evaluatology, which encompasses the science and engineering of evaluation. The science of evaluation addresses the fundamental question: ”Does any evaluation outcome possess a true value?” The engineering of evaluation tackles the challenge of minimizing costs while satisfying the evaluation requirements of stakeholders. To address the above challenges, we propose a universal framework for evaluation, encompassing concepts, terminologies, theories, and methodologies that can be applied across various disciplines, if not all disciplines.This is a short summary of Evaluatology (Zhan et al., 2024). The objective of this revised version is to alleviate the readers’ burden caused by the length of the original text. Compared to the original version (Zhan et al., 2024), this revised edition clarifies various concepts like evaluation systems and conditions and streamlines the concept system by eliminating the evaluation model concept. It rectifies errors, rephrases fundamental evaluation issues, and incorporates a case study on CPU evaluation (Wang et al., 2024). For a more comprehensive understanding, please refer to the original article (Zhan et al., 2024). If you wish to cite this work, kindly cite the original article.Jianfeng Zhan, Lei Wang, Wanling Gao, Hongxiao Li, Chenxi Wang, Yunyou Huang, Yatao Li, Zhengxin Yang, Guoxin Kang, Chunjie Luo, Hainan Ye, Shaopeng Dai, Zhifei Zhang (2024). Evaluatology: The science and engineering of evaluation. BenchCouncil Transactions on Benchmarks, Standards and Evaluations, 4(1), 100162.